KPI simulation method of harmonized communication and sensing in 6G - Zhonghua CHEN; Ling JIN; Jianping SUN (Dianxin kexue)
How to reasonably provide harmonized communication and sensing for different applications has become one of the important research directions of 5G network evolution and 6G technology.Based on the analysis of different scenarios and key performance indicators (KPIs), an architecture and brief realization including the implementation of each module of the harmonized communication and sensing simulation system was put forward.Furthermore, a correlation simulation case about communication spectrum efficiency and sensing range resolution was given to show how typical indicators work during the simulation under certain conditions.